Smart Navigation Of Wheel Chair Using Human Machine Interface - et. al., Rithik Richard, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This manuscript deals with smart navigation of wheelchair using human machine interface. Physically challenged people are those who suffer from different physical disabilities. In day-to-day life, physically challenged people are facing many problems and one of them being to move around without external support, being independent and the freedom to move around independently is an integral part of one’s life. This project is carefully designed by keeping in mind the problem's faced by physically challenged people. To implement the manuscript, Arduino UNO is used to control the motor coupled to the wheel of the wheelchair which is controlled by voice command from the android mobile phone through a Bluetooth module. Apart from moving the motor using voice command, the prototype also has an ultrasonic sensor which senses the obstacle on the way and controls the direction of the wheels accordingly. Apart from physically challenged people, aged people will also get benefited with this prototype.